Butadiene-Based Multidentate Ligand Formation via Stannylene Assisted C-C Coupling - Patel, Niranjan; Raut, Ravindra K.; Yildiz, Cem. B.; Majumdar, Moumita (Amer Chemical Soc, 2026)
Redox-active bis(alpha-iminopyridine) ligands L1 and L2 were reacted with Sn[N(SiMe3)2]2 in toluene at 60 degrees C to yield bisstannylene compounds 1 and 2 respectively. Both undergo C-C coupling between the methylene carbon atoms, generating a butadiene unit in the backbone. Compound 1 forms via intermolecular coupling, while compound 2 results from an intramolecular coupling. Ene-amide stabilized bisstannylene intermediates I1 and I2 were detected in in situ NMR spectroscopy and characterized by single crystal X-ray diffraction (SCXRD). The subsequent formation of an ene-amide stabilized monostannylene leading to compound 1 was studied by NMR. This monostannylene was trapped in its oxidized form using Ph2Se2 to give compound 3. Oxidation at the tin using Ph2Se2 during the formation of compound 2 produced tautomer 4, where the Sn(IV) is covalently bonded to L2 via carbon. Bisstannylene 5 supported by the C-C coupled ligand framework was isolated when BHT (BHT = 2,6-ditert-butyl-p-cresol) was added to the reaction mixture of 2. Demetalation with methanol or 4-methoxy phenol generated the organic molecules L3 and L4 as new multifunctionalized ligands. All of the compounds were characterized using single crystal X-ray diffraction, multinuclear NMR spectroscopy, mass spectrometry, and absorbance spectroscopy. Density Functional Theory (DFT) calculations were performed on relevant compounds.
Keywords: Complexes; Coordination; Tin; Hydrolysis; Zn